Colloid cysts of the third ventricle: correlation of MR and CT findings with histology and chemical analysis. - Maeder, P P; Holtås, S L; Basibüyük, L N; Salford, L G; Tapper, U A; Brun, A (American Journal of Neuroradiology, 1990)
Eight patients with colloid cysts of the third ventricle were examined with CT and MR. In six, surgical resection was performed and the material was subjected to histologic evaluation; the concentrations of trace elements were determined by particle-induced X-ray emission. Stereotaxic aspiration was performed in two. The investigation showed that colloid cysts are often iso- or hypodense relative to brain on CT (5/8), but sometimes have a center of increased density. Increased density did not correlate with increased concentration of calcium or other metals but did not correlate with high cholesterol content. Colloid cysts appear more heterogeneous on MR (6/8) than on CT (3/8), despite a homogeneous appearance at histology. High signal on short TR/TE sequences is correlated with a high cholesterol content. A marked shortening of the T2 relaxation time is often noticed in the central part of the cyst. Analysis of trace elements showed that this phenomenon is not related to the presence of metals with paramagnetic effects. Our analysis of the contents of colloid cysts does not support the theory that differing metallic concentrations are responsible for differences in MR signal intensity or CT density. We did find that increased CT density and high MR signal correlated with high cholesterol content.